Uranium adsorption by Articulospora tetracladia: can aquatic hyphomycetes be natural bioremediators of uranium contaminated streams? - Ferreira, V. (2009)
Uranium concentration in the streams around abandoned uranium mines in central Portugal can be as high as 1.8 mg/L. Herein we assessed the kinetics of uranium adsorption by Articulospora tetracladia mycelium at 200 and 2000 μgU/L over 6h. Uranium adsoption was relatively fast with 18–50% uranium remaining in solution after 15 minutes and maximum adsorption of ~140 mgU/gDM at 2000 μgU/L after 6h. The fitting of the uranium uptake data to the Freundlich isotherm indicates monolayer uranium adsorption at the surface of the mycelium. The stability of the uranium monolayer is high (n<1), as well as the adsorption capacity (at 1 μgU/L the uranium uptake is 1.73 mgU/gDM). Since the uranium uptake was not significantly different between live and dead mycelium, the uranium adsorption over the 6h study period was probably a physico-chemical process, independent of biological activity. The applicability of the Michaelis-Menten-type model indicates that adsorption at the mycelium surface progresses towards saturation, indicating that the limiting factor for uranium binding is the number of surface sites; maximum uranium uptake rate was 182 mgU/gDM, and 196 μgU/L was the half saturating uranium concentration. The high extraction factors (EF=28–41) and distribution coefficients (Kd>48203 mL/g) found for A. tetracladia indicate that this species can be considered a good biosorbent and has the ability to retrieve uranium from very dilute solutions (stream water). Aquatic hyphomycetes seem to have the potential to act as natural bioremediators of streams running through uranium contaminated areas.